Co-doping of magnesium with indium in nitrides: first principle calculation and experiment. Issue 6 (12th January 2016) - Liu, Zhiqiang; Fu, Binglei; Yi, Xiaoyan; Yuan, Guodong; Wang, Junxi; Li, Jinmin; Luna; Ferguson, Ian
Abstract : The valence band maximum could be modified by specific states coupling, thus improving the p-type dopability in In–Mg co-doping GaN. Abstract : In this work, an effective strategy for achieving efficient p-type doping in wide bandgap nitride semiconductors was proposed to overcome the fundamental issue of high activation energy. We demonstrated that a hole concentration as high as 1.4 × 10 18 cm −3 could been achieved through In–Mg co-doping. The electronic structure of the system and the formation energy of impurity were analyzed via first principle calculation to clarify the underlying physics and the ambiguity in understanding of the origin of the high hole concentration. Our results indicated that the original valence band maximum of the host materials could be modified, thus improving the p-type dopability. We showed that the calculated ionization energy ε (−/0) of acceptor is only about 135 meV, which is much smaller than that of the isolated Mg acceptor.